Pengaruh Model Kooperatif Tipe Think Talk Write Berbantuan Video Animasi Terhadap Aktivitas dan Hasil Belajar TIK Kelas VIII di SMPN 1 Pangkalan Kuras Kabupaten Palalawan - Safitri, Novia Irna; Rahmi, Ulfia; Eldarni, Eldarni; Zen, Zelhendri (Universitas PGRI Semarang, 2022)
The beginning of this research was due to students' problems with activities and student learning outcomes. During the passive student learning process,no one asked or contributed to the learning activity. Many student learning outcomes are less than the predetermined KKM value. This research was conducted with the aim of knowing the effect of using the Think Talk Write type learning model with the help of learning videos in ICT learning on the activities and learning outcomes of class VIII students. This research was conducted at SMPN 1 Pangkalan Kuras. This type of research is a quasi-experimental with a population of all class VIII SMPN 1 Pangkalan Kuras for the academic year 2021/2022 which opens seven classes. The sample is represented by class 8B as the experimental class and 8F as the control class. The sampling technique used was purposive sampling. The instruments used for data collection are questionnaires and tests. Data analysis used normality test and homogeneity test and t-test was performed to prove the hypothesis. The result is a significant effect of the use of the Think Talk Write cooperative learning model on activities and learning outcomes on basic computer operating materials taught using cooperative learning models and assisted by animated videos which are higher than student learning outcomes and learning motivation taught by learning models conventional video-assisted animation.